Implementasi Pembelajaran Multikultural untuk Membangun Karakter Peserta Didik MTs Assyifa Karang Sari - Praja Tuala, Riyuzen; Aini, Rizkya Fathiatul; Darma, Suria (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2025)
Multiculturalism is an understanding that emphasizes equality and equality of local cultures without ignoring the rights and existence of other cultures, which is important for us to understand together in the life of a multicultural society like Indonesia. Multicultural education can be formulated as a form of awareness about cultural diversity, human rights as well as reducing or eliminating all types of prejudice or prejudice to build a just and advanced society. Multicultural education can also be interpreted as a strategy to develop awareness of a person's pride in their nation. The aim of this research is to find out the implementation of multicultural learning to build the character of Madrasah students. In this research the research method used is a qualitative approach and descriptive analytical method. Data collection was carried out in 3 ways, namely, observation, interviews and documentation. The results of this research show that multicultural education can shape students' character starting by providing lessons about politeness and humanity, mutual respect, cooperation and tolerance, not discriminating, and so on.